Corporate Profitability and Firm Value Dynamics: The Moderating Effect of Dividend Policy in the Indonesian Consumer Non-Cyclicals Industry - Xevanya Melia Kadir; Hais Dama; Mohamad Agus Salim Monoarfa (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the effects of profitability and firm size on firm value, with dividend policy serving as a moderating variable, among non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The study employed a quantitative research approach using secondary data obtained from the companies’ annual financial reports. A purposive sampling technique was applied to select companies that met the predetermined criteria, resulting in a final sample of 26 companies with a total of 130 observations over five years. Data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the assistance of SmartPLS version 3.2.9. The findings indicate that profitability has a positive and significant effect on firm value, suggesting that companies with stronger financial performance are more likely to achieve higher market valuations. Firm size also has a positive and significant effect on firm value, implying that larger companies tend to gain greater investor confidence due to their operational stability and growth potential. Conversely, dividend policy has a negative and significant effect on firm value, indicating that higher dividend distributions may reduce investors’ expectations regarding future business expansion. Furthermore, the moderation analysis reveals that dividend policy is unable to strengthen or weaken the relationship between profitability and firm value, as well as the relationship between firm size and firm value. These findings contribute to the financial management literature by providing empirical evidence on the determinants of firm value and demonstrating the limited moderating role of dividend policy in non-cyclical consumer sector companies in Indonesia.